2006
DOI: 10.1007/s00726-006-0393-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of moderate and profound hypothermia on morphology, neurological, cognitive and behavioural functions in a rat model of perinatal asphyxia

Abstract: Hypothermia not only significantly increased survival, but also resulted in unimpaired motor as well as improved cognitive functions. Those findings are in contrast to altered brain morphology. As neuronal loss was present in various brain regions, we conclude that deficits may be compensated in the maturing animal. Intrahypoxic hypothermia was able to protect the rat from the devastating effect of perinatal asphyxia not in morphological, but in functional terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…Finally, when animals were downshifted from a 32% to a 4% sucrose solution, an attenuated suppression of consummatory behavior was observed in PA rats (Galeano et al, 2011). Despite of these behavioural impairment, neurological motor conditions were comparable to those of normoxic animals, in agreement with results obtained by Hoeger et al (2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, when animals were downshifted from a 32% to a 4% sucrose solution, an attenuated suppression of consummatory behavior was observed in PA rats (Galeano et al, 2011). Despite of these behavioural impairment, neurological motor conditions were comparable to those of normoxic animals, in agreement with results obtained by Hoeger et al (2006).…”
Section: Discussionsupporting
confidence: 91%
“…From a motor point of view, it should be noted that deficits, possibly linked to cerebellar lesions, are observed at very early stages ranging from days to several weeks (Young et al, 1986) but seem to be compensated 3 months after PA (Hoeger et al, 2006). These findings are in line with observations made in humans by Allin et al who reported no correlation between the volume of the underdeveloped cerebellum in preterm children and motor function later in Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hypothermia and hyperthermia have been shown to protect against and worsen hypoxia/ischemia induced CNS damage, respectively, in perinatal animals, and hypothermia is currently being used clinically to lessen asphyxia-induced brain damage in human neonates (Laptook and Corbett, 2002;Tomimatsu et al, 2003;Cebral et al, 2006;Gunn and Thoresen, 2006;Hoeger et al, 2006). We show that the anoxia-dependent decrease in IL-1b protein was attenuated by carrying out the anoxia under hypothermic conditions compared with normothermia.…”
Section: Discussionmentioning
confidence: 85%
“…Weitzdörfer et al interpreted this finding as a result of both altered neurotransmitter release and compensatory synaptogenesis following PA [52]. The Swedish experimental model was selected for this study for its suitability to evaluate morphology, metabolism, neurochemistry, and long-term effects of PA [54]. …”
Section: Effects Of Experimental Perinatal Asphyxia On Synaptic Ormentioning
confidence: 99%